Analyzing the Disillusionment in Ernest Hemingway’s The Sun Also Rises and Its Implication on English Language Learning - Herminus Efrando Pabur; Muhammad Ilham Ali; Sabrina W. J. Husain; Fivy A. Andries; Jennie Posumah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The Sun Also Rises, written by Ernest Hemingway in 1926, is an influential literary work that depicts the post-war Lost Generation. The novel captures the profound sense of disillusionment experienced by individuals from the Lost Generation coping with the collapse of traditional values. The present study aims at analyzing the disillusionment depicted by the character of Jake Barnes in Ernest Hemingway’s The Sun Also Rises and its implication on English language learning. This qualitative research is conducted by using Hemingway’s The Sun Also Rises as the primary data and is supported by secondary data in the form of academic papers, research papers, and books related to the topic of disillusionment in literary works. To collect data, the researchers employed the observation and note-taking technique in which the researcher read the novel several times and took notes related to the topic of disillusionment. The obtained data were analyzed using an objective approach focusing on character development, narrative structure, and symbolic elements. The findings show that Jake Barnes, the protagonist in The Sun Also Rises, experiences the disillusionment in the form of disappointment caused by the aftermath of World War I. He shows his disappointment towards himself and the other character in the novel, as shown in the dialogues and descriptions in the novel. The study suggests that The Sun Also Rises can be utilized for English language learning in which both students and teachers can benefit by the use of the novel as a learning media, learning sources and learning object.